An Analysis of High Resolution Computed Tomography Chest Imaging Features of Covid-19 Pneumonia in Immunocompetent and Immunocompromised Patients - Aishitha, Salavakam; M.G. Ravi; Baru, Rama Krishna Rao; Madhusudana, Yarramsetti (Asian Journal of Medical Radiological Research, 2023)
Background: The Coronavirus disease 2019 (COVID-19) is caused by the novel coronavirus severe acute respiratory syndrome (SARS) CoV-2. Immune system dysfunction increases susceptibility to infections. Due to the ongoing environmental exposure of the respiratory tract, pulmonary infections are highly frequent and relatively more severe in immunocompromised people. Also, immunocompromised people are susceptible to opportunistic infections in addition to the common diseases that can infect an immunocompetent person. The gold standard diagnostic test for corona virus pneumonia is the molecular detection of SARS-CoV-2 nucleic acid. On CT, patients with COVID-19 displayed typical characteristics, such as bilateral multilobar ground-glass opacities with a posterior or peripheral predominance. The current study is to help us look for the types and severity of the changes in the chest CT imaging brought by the disease and how it varies in immunocompromised patients of COVID-19. Subjects and Methods: This is a hospital based comparative study design with a sample size of 91 patients referred to the department of Radiodiagnosis. Narayana Medical College, Nellore. The study was conducted for a period of 12 months. Results: Of 91 patients who tested RTPCR positive for SARS-CoV-2, 74 (81.31%) patients showed features of COVID -19 pneumonia on HRCT and 17 (18.68%) patients had no chest CT features. Among these 91 patients, 40 were immunocompromised and 51 were immunocompetent. Of the 17 patients with no CT changes, 13 (76.4%) were immunocompetent, and 4 (23.6%) were immunocompromised. Of the 51 immunocompromised patients, 42 had uncontrolled diabetes, 12 patients had chronic kidney disease, 1 patient had acquired immunodeficiency syndrome due to human immunodeficiency virus. 5 patients had both diabetes mellitus and chronic kidney disease. Most of the patients with no immunocompromising co-morbidities showed mild changes (35.0%) followed by no changes (32.5%). 25.0% of these patients showed moderate changes and 7.5% showed severe changes. Majority of the patients with diabetes (45.23%) showed moderate changes, followed by severe and mild changes. Majority of the patients (66.66%) with chronic kidney disease showed moderate changes, followed by severe changes in 16.6%. Conclusion: Patients with immunosuppressing conditions such as diabetes mellitus and chronic kidney disease had significantly more severe CT scores as compared to patients with no such background. Immunosuppressed patients are at higher risk for more severe corona virus disease and complications such as pneumothorax and pneumomediastinum. High Resolution CT is an important imaging modality to determine the disease extent and severity. Prioritizing those patients who have COVID-19 and immunosuppression is crucial since the severity of HRCT results has been shown to be higher in these patients.